Head and neck trauma in a rapidly growing African metropolis: a two-year audit of hospital admissions - Minja, Irene Kida; Wilson, Michael; Shaikh, Masood; Perea-Lowery, Leila (International journal of environmental research and public health, 2019)
Understanding injury-related burdens is an essential part of trauma quality improvement programs aimed at decreasing morbidity and mortality. This is especially the case in low and middle-income country settings where data on injuries remains limited. The aim of this study was to audit the types of head and neck injuries, which have been diagnosed among patients admitted to a major national hospital in the context of a rapidly growing sub Saharan city. Data were collected retrospectively for head and neck trauma from the Muhimbili National Hospital (MNH) in Dar es Salaam, Tanzania from the years 2016 and 2017. Distribution of ICD-10 codes by age and sex for the five most common diagnoses were determined using frequencies and percentages. The most common diagnosis was ICD-10-S02 (fracture of skull and facial bones) with 277 cases (44.1%), which was followed by S05 (injury of the eye and orbit), 114 cases (18.2%), and S09 (other and unspecified injuries of head) 77 cases (12.3%). The mean ages of admission for these three diagnoses were 28.1 (SD: 11.6), 23.8 (SD: 18.9), and 30.8 (SD: 18.0) years, respectively. This study provides information on the overall burden of head and neck trauma at a major regional tertiary care facility. It provides an initial understanding of the burden of head and neck trauma and suggests follow-up in the form of clarification of injury mechanisms and contextual factors for future work.
Gesehen am 07.05.2020